2022
DOI: 10.1002/naaq.10250
|View full text |Cite
|
Sign up to set email alerts
|

Dietary Sodium Butyrate Supplementation Attenuates the Detrimental Effects of High‐Fat Diets on Growth Performance, Liver Health, and Disease Resistance in Grass Carp

Abstract: An 8‐week experiment was conducted to investigate the effects of sodium butyrate (NaBT) inclusion in high‐fat (HF) diets on growth performance, liver health, and disease resistance in Grass Carp Ctenopharyngodon idella. Three diets (Control diet containing crude lipid at 58 g/kg, HF diet with 108‐g/kg crude lipid, and NaBT diet with 108‐g/kg crude lipid and 1‐g/kg NaBT) were randomly assigned to nine tanks with 30 fish (9.50 ± 0.06 g) in each tank. After the feeding trial, disease resistance was assessed by in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(2 citation statements)
references
References 69 publications
(149 reference statements)
1
1
0
Order By: Relevance
“…Fang et al (78) and Ullah et al (82) found that SB reduced the HSI, which is consistent with the results of the present study, and may be related to the reduction of lipid content in the livers of largemouth bass by sodium butyrate. As in the present study, SB reduced TG content in the liver of largemouth bass (79), and additional SB supplementation reduced TG in grass carp on a high-fat diet (80). However, the underlying mechanism of sodium butyrate's effects on lipid metabolism in aquatic animals remains to be elucidated.…”
Section: Itemsupporting
confidence: 51%
“…Fang et al (78) and Ullah et al (82) found that SB reduced the HSI, which is consistent with the results of the present study, and may be related to the reduction of lipid content in the livers of largemouth bass by sodium butyrate. As in the present study, SB reduced TG content in the liver of largemouth bass (79), and additional SB supplementation reduced TG in grass carp on a high-fat diet (80). However, the underlying mechanism of sodium butyrate's effects on lipid metabolism in aquatic animals remains to be elucidated.…”
Section: Itemsupporting
confidence: 51%
“…Hepatic lipid deposition often occurs in cultured fish, and is closely related to metabolic disorders [ 39 ]. In this experiment, the TC and TG levels in the liver were significantly higher in the AGPAT2 knock-down group than in the control groups.…”
Section: Discussionmentioning
confidence: 99%